2011
DOI: 10.1159/000327388
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Elution and Mechanical Properties of Two Injectable Chemotherapeutic Bone Cements

Abstract: Chemotherapeutic bone cements can both stabilize the bone fractures as well as deliver chemotherapy agents directly to the bone metastatic site and adjacent soft tissue tumors. This study evaluated the in vitro elution and flexural properties of Vertebroplastic™ and Confidence Ultra™ bone cements (Depuy Spine Inc., Raynham, Mass., USA) containing methotrexate. In vitro elution was measured by placing bone cement specimens containing 4 different methotrexate amounts in 20 ml saline, and the methotrexate elution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…Using two commercially available acrylic bone cements (Vertebroplastic TM and Confidence Ultra TM ) loaded with methotrexate at varying amounts, the same authors found a correlation between MTX elution and a decrease in flexural modulus as well as cement strength. This decrease was not proportional to the initial amount of MTX added [210]. Different concentrations of DOX and pamidronate were incorporated within surgical Simplex™ acrylic cement in order to study their influence on cement mechanical properties and their in vitro release.…”
Section: Drug-releasing Intraosseous Implantsmentioning
confidence: 99%
“…Using two commercially available acrylic bone cements (Vertebroplastic TM and Confidence Ultra TM ) loaded with methotrexate at varying amounts, the same authors found a correlation between MTX elution and a decrease in flexural modulus as well as cement strength. This decrease was not proportional to the initial amount of MTX added [210]. Different concentrations of DOX and pamidronate were incorporated within surgical Simplex™ acrylic cement in order to study their influence on cement mechanical properties and their in vitro release.…”
Section: Drug-releasing Intraosseous Implantsmentioning
confidence: 99%
“…However, fabrication of controlled drug release system based on CPCs is critical. Where either very low or accelerated drug elution is undesirable, so that the drug should be release with a rate that achieve a disease treatment [22]. Accordingly, the drug delivery system can be tailored by adjusting porosity, particle size, incorporation of other materials to obtain composites etc.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 1 depicts an overview of the analyses carried out in this work. While prior studies have investigated antineoplastic drug-laden PMMA, [30][31][32][33][34][35][36][37][38][39][40] our work is the first to evaluate release kinetics and material/structural properties of DOX-laden PMMA bone cement and to devise a localized adjuvant chemotherapeutic delivery platform to be integrated into temporary spacers for use in the Masquelet technique, offering a potential adjunct to supplement systemic adjuvant chemotherapy. The goal of this study is to evaluate the feasibility of using a PMMA composite chemotherapeutic delivery system for temporary spacer applications for bone reconstruction procedures that is capable of releasing its entire payload and meets mechanical standards.…”
Section: Introductionmentioning
confidence: 99%